Programa ProJovem adolescente : um olhar a partir da teoria crítica de Honneth - Morgan, Marisa Ignes Orsolin (2014)
This thesis proposes, from the analysis of the structural axis and methodological dimensions Projovem Adolescent Program, foregrounding the social and educational dimension of the program as proposed handles non-formal education to the Theory of recognition Honneth. Explored as a reference for research, aspects of political and social identity of the program based on an analysis of its main principles in order to situate the methodological dimensions that underlie social and educational activities undertaken by the program under study and indicate how socio methodological dimensions of the program can be understood as possible potentiating the quest for recognition from reading what we make it through the critical theory Honneth. Our effort is, ultimately, to show that the Projovem Adolescent, while non-formal educational program, has a potential for intersubjective recognition can contribute to identity formation, socialization and social inclusion. To realize the goal set is a part-documentary research based on official documents about Projovem Adolescent and documents of national social welfare policy and the like. The documentary dimension articulates the literature as analytical-reconstructive procedure in this work is based on a clipping from the work of Honneth and productions on the theme of recognition in the field of social sciences and philosophy, as well as studies that address education non-formal directly or indirectly, as a Gohn and Caliman